A layered Bi2Te3 nanoplates/graphene composite with high gravimetric and volumetric performance for Na-ion storage. Issue 11 (17th September 2019) - Sun, Dianding; Zhang, Guanjun; Li, Dan; Liu, Sitong; Jia, Xiaolong; Zhou, Jisheng
Abstract : A one-pot solvothermal method was used to prepare a layered Bi2 Te3 nanoplates/graphene composite with outstanding gravimetric and volumetric Na-ion storage performance. Abstract : Exploring new electrode materials with both high gravimetric and volumetric Na-ion storage performances is urgently desired but still faces significant challenges. In this work, a composite of layered Bi2 Te3 nanoplates/graphene, which is denoted as Bi2 Te3 /G, was synthesized by a one-pot solvothermal method. Here, Bi2 Te3 nanoplates with a large interlayer spacing of 1.02 nm were uniformly anchored on graphene with strong interfacial interaction. The obtained Bi2 Te3 /G composite exhibited high reversible gravimetric capacity of 416 mA h g −1 at 0.1 A g −1 and an excellent rate performance. Even at 5.0 A g −1, Bi2 Te3 /G still delivered a gravimetric capacity as high as 203 mA h g −1 . Due to its high tap density of 1.56 g cm −3, Bi2 Te3 /G also delivered impressive volumetric capacities. The reversible volumetric capacity was as high as 648.9 mA h cm −3 at 0.1 A g −1 . At 5 A g −1, Bi2 Te3 /G still retained volumetric capacity of 316.7 mA h cm −3 . The excellent gravimetric and volumetric Na-ion storage performances of the Bi2 Te3 /G composite should be ascribed to the quintuple layer sandwich structure of Bi2 Te3, the synergistic effect between Bi2 Te3 and graphene, and its higher density. Accordingly, the Bi2 Te3 /G composite is expected to exhibit great application prospects as a promising anode candidate for smart sodium-ion batteries.